Cucurbituril Ameliorates Liver Damage Induced by Microcystis aeruginosa in a Mouse Model - Saleh, Na'il; Al-Jassabi, Saad; Eid, Ali H.; Nau, Werner M. (Frontiers in Chemistry, 2021)
Microcystis aeruginosa is a cyanobacterium that produces a variety of cyclic heptapeptide toxins in freshwater. The protective effects of the macromolecular container cucurbit[7]uril (CB7) were evaluated using mouse models of cyanotoxin-induced liver damage. Biochemical analysis of liver function was performed to gauge the extent of liver damage after exposure to cyanobacterial crude extract [CCE; LD50 = 35 mg/kg body weight; intraperitoneal (i.p.)] in the absence or presence of CB7 (35 mg/kg body weight, i.p.). CCE injection resulted in liver enlargement, potentiated the activities of alanine aminotransferase (ALT) and glutathione S-transferase (GST), increased lipid peroxidation (LPO), and reduced protein phosphatase 1 (PP1) activity. CCE-induced liver enlargement, ALT and GST activities, and LPO were significantly reduced when CB7 was coadministered. Moreover, the CCE-induced decline of PP1 activity was also ameliorated in the presence of CB7. Treatment with CB7 alone did not affect liver function, which exhibited a dose tolerance of 100 mg/kg body wt. Overall, our results illustrated that the addition of CB7 significantly reduced CCE-induced hepatotoxicity (P < 0.05).